The Asian waterfowl census 1987-91 : (International Waterfowl and Wetlands Research Bureau, 1994)
This document presents the findings of the most comprehensive census ever carried out on Asian waterfowl. Over 3,000 wetlands in 32 countries were assessed; distribution maps for 200 commonly recorded species are presented, with the most important sites identified for each species; sites of international importance using the Ramsar 1% criterion are also identified. Some 496 wetlands were identified as being of international importance. A key conservation document for the region.